Application of the Weighted Product Model Method for Vendor Selection at PT. Indonesia Comnets Plus - Nur Rofiq; Puji Raja Bagus Kausar (Jurnal Inotera, 2024)
PLN Icon Plus is a subsidiary of PLN which runs its business in the telecommunications sector as an internet service provider (ISP) requiring collaboration with vendors in various aspects of work. In order to fulfill work functions quickly and precisely and efficiently in the costs incurred, selection is required, so that the results of the work and the costs incurred can reach the target. This problem may require the implementation of a system that can help make decisions in the vendor selection process, namely a decision support system (DSS) with the Weighted Product (WP) method. WP is a popular multi-criteria analysis decision and this method is also based on computational complexity that is not too difficult so the time required to produce calculations is relatively short. The results of this research were obtained from calculating several criteria factors such as legality of PT, Evidence of Technical Qualifications, Unit Specifications, Price and Track Record, resulting in the ranking process within the scope of PT. PLN Icon Plus produces the vector V1 value as the highest value, namely 0.238. This value is an alternative to PT. Sanestri Bangun Jaya (SBJ). The Decision Support System (SPK) which was developed based on a website and has carried out black box testing shows that the system developed has worked well.